Heart Rate and Systolic Blood Pressure in Patients with Persistent Atrial Fibrillation - Corino, V. D. A.; Belletti, S.; Terranova, P.; Lombardi, F.; Mainardi, L. T. (Methods of Information in Medicine, 2010)
Background: During atrial fibrillation (AF), ventricular response is highly irregular and thus the beat-to-beat variation of blood pressure is increased because of variations in filling time and in contractility.Objectives: Aim of the present study is to investigate the short-term dynamics of RR and SAP series in patients with AF, during rest and tilt, and after restoration of sinus rhythm. Methods: We computed symbolic sequences of the three phases, as they retain important features of the dynamics generated by the underlying control system. Then we applied a method based on rank order statistics of symbolic sequences to investigate the profile of different types of dynamics. The linguistic distance (range 0–1) between sequences represents a measure of similarity to assess whether the different physiological states are reflected on the dynamics of RR and SAP series.Results: The distance between rest and tilt phases is 0.06 ± 0.02 for RR series, meaning they are very similar, while it is 0.21 ± 0.13 for SAP series, showing a difference in the short-term dynamics. RR mean decreases during tilt (738 ± 164 vs. 692 ± 152 ms, p < 0.05, rest vs. tilt), while mean SAP is not significantly different (101 ± 20 vs. 104 ± 14 mmHg, rest vs. tilt). Comparing AF and sinus rhythm, both RR and SAP series result different in terms of the computed distance.Conclusions: SAP short-term dynamics seem to significantly change when comparing rest and tilt phases, while RR series remain unchanged. Moreover, RR mean but not SAP series significantly decreases during tilt.
Keywords: Atrial fibrillation; blood pressure; degree of nonrandomness; heart rate variability; linguistic analysis